2013 Winter Simulations Conference (WSC) 2013
DOI: 10.1109/wsc.2013.6721626
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of evaluation methods for police patrol district designs

Abstract: Police patrol district design presents a multi-objective optimization problem with two goals: minimizing workload variation between patrol districts and minimizing the response time for officers responding to calls for service. We evaluate three different methods for scoring district designs: a closed form probability based approach, a discrete-event simulation based on hypercube models for spatial queuing systems, and an agent-based simulation model. We find that all methods provide similar evaluations when s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…Instead of tick-by-tick evaluation of police cars’ state variables in the agent-based model, the discrete-event simulation in Zhang et al updates police cars’ status only when they get calls, arrive at scenes, leave scenes and return to patrol states. 25 The travel times are modeled using Euclidean distance and responding speed affected by overall traffic conditions at a different time of day. The generation of CFS incidents is the same as that used in the agent-based model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of tick-by-tick evaluation of police cars’ state variables in the agent-based model, the discrete-event simulation in Zhang et al updates police cars’ status only when they get calls, arrive at scenes, leave scenes and return to patrol states. 25 The travel times are modeled using Euclidean distance and responding speed affected by overall traffic conditions at a different time of day. The generation of CFS incidents is the same as that used in the agent-based model.…”
Section: Introductionmentioning
confidence: 99%
“…The generation of CFS incidents is the same as that used in the agent-based model. The discrete-event simulation runs much faster than the agent-based model and provides a similar districting plan evaluation under low and median CFS incidents intensity levels 25 .…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al (2013) [32] The focus of this research is the evaluation of three different methods for scoring police districting designs: a closed form probability based approach, a discrete-event simulation based on hypercube models for spatial queuing systems, and an agentbased simulation model. The scoring measures are evaluated on designs generated using the methodology presented in Zhang and Brown (2013) [29].…”
Section: Wang (2012) [28]mentioning
confidence: 99%
“…I would like extend this work to analyze the performance of prediction models that use a non-uniform grid. Moreover, researchers in [79] found that the temporal component can have a significant impact of three evaluation metrics used for scoring district designs. Motivated by their work, I would like to extend this analysis to study the impact of changing the prediction window (e.g., one day to one week) on evaluation metrics.…”
Section: Summary Of Future Workmentioning
confidence: 99%